COMT Effects on Vitamin E and Colorectal Cancer, in-vitro and in Two Randomized Trials (P15-005-19). (13th June 2019) - Hall, Kathryn; Weinstein, Stephanie; Buring, Julie; Mukamal, Kenneth; Moorthy, M Vinayaga; Ridker, Paul; Albanes, Demetrius; Cook, Nancy; Chasman, Daniel; Sesso, Howard
Abstract: Objectives: Despite promising observational data and compelling mechanisms of action, vitamin E has failed to demonstrate evidence of benefit in randomized clinical trials (RCTs). In two large long-term placebo-controlled RCTs, we reported that vitamin E effects on total cancer were modified by genetic variation in catechol-O-methyltransferase (COMT), an enzyme that metabolizes catecholamines. Here we investigate COMT effects on colorectal cancer (CRC) in the two RCTs and a CRC cell line. Methods: We analyzed COMT rs4680 association with rates of CRC in the Women's Health Study (WHS), N = 23, 294 and a case/control ( N = 2396/2235) subset of the Alpha-Tocopherol Beta-Carotene Cancer Prevention Study (ATBC). Cell survival and apoptosis were examined in-vitro in HCT116 cells treated with increasing doses of vitamin E when COMT gene expression was inhibited by silencing RNA (siRNA). Results: Rates of CRC were higher with randomized vitamin E compared to placebo among COMT high-activity val/val homozygotes in ATBC (HR, [CI] = 3.00, [1.48–6.09]), but not WHS (HR, [CI] = 0.99, [0.63–1.57]). Among low-activity met/met homozygotes randomized to vitamin E compared to placebo, rates of CRC were borderline lower in WHS (HR, [CI] = 0.66, [0.44–1.01]), but not in ATBC (HR, [CI] = 0.93, [0.63–1.62]). In cell culture, vitamin E at 3 µg/ml and 10 µg/mL had no effect on cell viability or apoptosis. However, silencing COMT resulted in a modest apoptotic effect that vitamin E enhanced in a dose-dependent manner. Human apoptosis arrays indicated that in the absence of COMT expression, vitamin E induced protein expression related to the intrinsic apoptotic pathway through p53 activation, dysregulation of Bcl-2 family protein expression and down-regulation of IAP family protein expression. Conclusions: Differential COMT effects on vitamin E and CRC were similar to those previously reported for all invasive cancers, but were only significant for val/val homozygotes. Further, inhibiting COMT in the presence of vitamin E in a CRC in-vitro model, recapitulated the RCT observation that among individuals homozygous for the low-activity allele (met/met) vitamin E tended to reduce invasive cancer and here CRC. Funding Sources: National Institutes of Health: NCI and NHLBI.